2023
DOI: 10.1523/jneurosci.0112-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Speech Reception in Young Children with Autism Is Selectively Indexed by a Neural Oscillation Coupling Anomaly

Xiaoyue Wang,
Jaime Delgado,
Silvia Marchesotti
et al.

Abstract: Communication difficulties are one of the core criteria in diagnosing ASD, and are often characterized by speech reception difficulties, whose biological underpinnings are not yet identified. This deficit could denote atypical neuronal ensemble activity, as reflected by neural oscillations. Atypicalcross-frequency oscillation coupling,in particular, could disrupt the joint tracking and prediction of dynamic acoustic stimuli, a dual process that is essential for speech comprehension. Whether such oscillatory an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 113 publications
1
6
0
Order By: Relevance
“…Audio-visual processing, especially the synchronization of the two sensory modalities, plays a pivotal role in understanding the communicative challenges observed in ASD. Previous studies have established that basic auditory dysfunctions and atypical speech processing are characteristic of ASD from an early developmental stage (1924). Our study reveals that such anomalies are not merely isolated auditory deficits but are deeply connected to the integration of auditory and visual information, a process critical for effective communication, particularly in dynamic or complex listening environments (93,94).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Audio-visual processing, especially the synchronization of the two sensory modalities, plays a pivotal role in understanding the communicative challenges observed in ASD. Previous studies have established that basic auditory dysfunctions and atypical speech processing are characteristic of ASD from an early developmental stage (1924). Our study reveals that such anomalies are not merely isolated auditory deficits but are deeply connected to the integration of auditory and visual information, a process critical for effective communication, particularly in dynamic or complex listening environments (93,94).…”
Section: Discussionmentioning
confidence: 99%
“…The reset of auditory neural oscillations triggered by visual input (65) rhythmically enhances auditory processing (66), a phenomenon that is already observable in typical children (67). Despite the documented presence of auditory processing anomalies in ASD around 3-year-old (24), we still ignore whether they are associated with dynamic audio-visual synchrony anomalies.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Research found that children with ASD have elevated relative efficacy in the δ, θ (4-8 Hz), α (8-12 Hz), Β, and γ bands, decreased θ/Β ratios in frontal regions, enhanced θ/Β ratios in Cz and Pz electrodes, and significant correlations between θ/Β and cognitive function ( 91 ). The hierarchical processing of phonemic and syllable range information (θ/γ coupling) is disrupted in children with ASD, which may account for communication difficulties in children with impaired speech reception ( 92 ). Total lobe alpha power is lower in children with ASD than in neurotypical children ( 93 ), whereas long-distance intra- and inter-hemispheric connectivity is improved after transcranial magnetic stimulation (rTMS) interventions, especially within the alpha band, while local and global network properties are greatly enhanced in the δ, θ, and α bands ( 94 ).…”
Section: Neural Pathwaysmentioning
confidence: 99%